Evaluation of hydroponic techniques for terrace cultivation of vegetable crops - ASLAM C SABITHA R SHIYA PAUL V JAGATH K. M; Dr. Rema K. P (Guide) (Tavanur 2016 Kelappaji college of Agricultural Engineering and Technology)
soil fertility decline and development of salinity have been a matter of concern. the study compared the effects of three different hydroponic systems on the growth and yield of amaranthus.
Evaluation of hydroponic techniques for terrace cultivation of vegetable crops